Welcome to Westonci.ca, where curiosity meets expertise. Ask any question and receive fast, accurate answers from our knowledgeable community. Join our Q&A platform and get accurate answers to all your questions from professionals across multiple disciplines. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
To determine which graph represents the solution set of the equations \( y = x^2 - 4 \) and \( x + y + 2 = 0 \), let’s solve these equations step by step.
### 1. Expressing \( y \) from one of the equations:
From the second equation \( x + y + 2 = 0 \):
[tex]\[ y = -x - 2 \][/tex]
### 2. Substitute \( y = -x - 2 \) into the first equation \( y = x^2 - 4 \):
[tex]\[ -x - 2 = x^2 - 4 \][/tex]
### 3. Rearrange the equation:
[tex]\[ x^2 + x - 2 = 0 \][/tex]
### 4. Solve the quadratic equation \( x^2 + x - 2 = 0 \):
To solve \( x^2 + x - 2 = 0 \), we can factorize it as:
[tex]\[ (x + 2)(x - 1) = 0 \][/tex]
So, the solutions for \( x \) are:
[tex]\[ x + 2 = 0 \quad \Rightarrow \quad x = -2 \][/tex]
[tex]\[ x - 1 = 0 \quad \Rightarrow \quad x = 1 \][/tex]
### 5. Find the corresponding \( y \)-values using \( y = -x - 2 \):
For \( x = -2 \):
[tex]\[ y = -(-2) - 2 = 2 - 2 = 0 \][/tex]
For \( x = 1 \):
[tex]\[ y = -(1) - 2 = -1 - 2 = -3 \][/tex]
### 6. Summary of solutions:
The solutions to the system of equations are:
[tex]\[ (x, y) = (-2, 0) \quad \text{and} \quad (1, -3) \][/tex]
### Interpretation:
On a graph, this means the points \((-2, 0)\) and \((1, -3)\) must satisfy both equations.
To decide between graph II and graph III, you should check these points on the graphs. The graph that shows these intersection points accurately represents the solution set of the given equations.
### 1. Expressing \( y \) from one of the equations:
From the second equation \( x + y + 2 = 0 \):
[tex]\[ y = -x - 2 \][/tex]
### 2. Substitute \( y = -x - 2 \) into the first equation \( y = x^2 - 4 \):
[tex]\[ -x - 2 = x^2 - 4 \][/tex]
### 3. Rearrange the equation:
[tex]\[ x^2 + x - 2 = 0 \][/tex]
### 4. Solve the quadratic equation \( x^2 + x - 2 = 0 \):
To solve \( x^2 + x - 2 = 0 \), we can factorize it as:
[tex]\[ (x + 2)(x - 1) = 0 \][/tex]
So, the solutions for \( x \) are:
[tex]\[ x + 2 = 0 \quad \Rightarrow \quad x = -2 \][/tex]
[tex]\[ x - 1 = 0 \quad \Rightarrow \quad x = 1 \][/tex]
### 5. Find the corresponding \( y \)-values using \( y = -x - 2 \):
For \( x = -2 \):
[tex]\[ y = -(-2) - 2 = 2 - 2 = 0 \][/tex]
For \( x = 1 \):
[tex]\[ y = -(1) - 2 = -1 - 2 = -3 \][/tex]
### 6. Summary of solutions:
The solutions to the system of equations are:
[tex]\[ (x, y) = (-2, 0) \quad \text{and} \quad (1, -3) \][/tex]
### Interpretation:
On a graph, this means the points \((-2, 0)\) and \((1, -3)\) must satisfy both equations.
To decide between graph II and graph III, you should check these points on the graphs. The graph that shows these intersection points accurately represents the solution set of the given equations.
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.